Highly sensitive detection of carbendazim in juices based on mung bean-derived porous carbon@chitosan composite modified electrochemical sensor. (30th October 2022) - Liu, Runqiang; Chang, Yuqi; Li, Fang; Dubovyk, Volodymyr; Li, Dongdong; Ran, Qiwen; Zhao, Hongyuan
Highlights: MBC@CTS composite was prepared by a simple and scalable strategy. MBC@CTS/GCE sensor was fabricated for the sensitive detection of carbendazim. Synergistic effect of MBC and CTS enhanced the carbendazim detection performance. A low limit of detection (20 nM) was achieved at the MBC@CTS/GCE sensor. MBC@CTS/GCE sensor showed good practical feasibility in juice samples. Abstract: We reported a simple and scalable strategy for the preparation of mung bean-derived porous carbon@chitosan (MBC@CTS) composite, which was used to optimize the glassy carbon electrode (GCE). The MBC@CTS/GCE sensor was applied for the carbendazim (CBZ) detection. For the MBC@CTS composite, MBC with three-dimensional hierarchical structure presented large specific surface area, good adsorbability, and high electrical conductivity, while CTS had good film-forming property, hydrophilicity performance, and adhesion capacity. The MBC@CTS/GCE sensor exhibited wonderful electrochemical detection performance towards CBZ. Under the optimized conditions, the MBC@CTS/GCE sensor showed a linear concentration range from 0.1 to 20 μM with relatively low limit of detection (LOD) of 20 nM. In addition, the fabricated sensor with good reproducibility, stability, and selectivity were successfully applied for the CBZ detection in apple and tomato juices with low relative standard deviation of 2.4 %–4.2% and satisfactory recoveries of 98.8–103.2%.